Analisis Perbandingan Pengaruh Performa Aliran Natural dan Penggunaan Sluice Gate (Pintu Air) Pada Kincir Air Dengan Pendekatan Kajian Teoritis - Ridho Dwi Syahrial; Muhammad Helmi Kurniawan; Khusnul Khotimah Ayuningtiyas (Universitas Bojonegoro, 2022)
The water wheel is defined as a mechanical device in the form of a wheel with blades (buckets or spatulas) around the edges which are on the horizontal axis of water as the working fluid. The water flowing into and out of the wheel has no excess pressure, only atmospheric pressure. The speed of the water flowing into the wheel must be large, because if the speed is large, the impetus on the blades of the water wheel will be greater. Comparison of the Effect of Natural Flow Performance and the Use of Sluice Gate on the Wheel. The use of Sluice Gate on the Waterwheel affects the performance of the waterwheel and from several variations in the width of the sluice gate flow gap (25mm), (35mm), and (40mm) with a sluice gate flow gap of 40 mm with an efficiency of 38.12 % at 40 rpm rotation, which is 13 Watt higher than the natural flow test at 40 rpm, the rotation speed is 5.11 watts with an efficiency of 10%, and the lowest power at 10 rpm is 3 watts and an efficiency of 6% with a discharge of 12 liters per second.